The Moderating Role of Stakeholder Involvement in the Relationship Between Strategic Planning And Service Delivery - Keranga, Bahati; Ogutu, Martin; Awino, Zachary; Njeru, Winnie (International Journal of Scientific Research and Management (IJSRM), 2021)
In keeping with the New Public Management dispensation, state corporations in Kenya have taken up strategic planning with a view to effect reforms for improved service delivery. New Public Management particularly advances a customer-centric approach to public administration for improved service delivery, with the public, who are the recipients of public service, as key stakeholders in public administration. Despite this, service delivery in the Agribusiness sub-sector in the country is riddled with inadequacies highlighted by among other complaints, unpaid produce supplies, dwindling finances, slumped agricultural extension services and low produce prices. Against this backdrop, the study set out to establish the effect of strategic planning on service delivery and assess how stakeholder involvement influences the relationship between strategic planning and service delivery among agribusiness state corporations in Kenya. Grounded on the New Public Management and Stakeholder theories, the study adopted the positivism paradigm and the descriptive cross-sectional research design. Targeting 73 state corporations pertinent to agribusiness in the country, primary data was collected by use of a structured questionnaire with institutional heads as the units of observation. Both descriptive and inferential statistics were then employed in data analysis. It was established that strategic planning has a significant positive influence on service delivery. Stakeholder involvement was however found to not have a significant moderating effect on the relationship between strategic planning and service delivery. This was attributed to the technocratic approach in the formulation of the strategic plans among state corporations and the numerically limited nature of most stakeholders in state corporations represented in the boards of directors. Following a significant direct effect of stakeholder involvement on service delivery among Agribusiness state corporations in the country, state corporations are implored to involve stakeholders in strategic planning and observe meaningful participation, communication and dispute resolution in the engagement.